The Objectives of Law from a Juridical-Normative Perspective and Their Implications in the Contemporary Era - Jumriani J; Abd. Halim Talli; Zulhas’ari Mustafa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines how the juridical-normative perspective and the concept of maqÄá¹£id al-sharÄ«â€˜ah work together to understand the objectives of law in the contemporary era. While maqÄá¹£id al-sharÄ«â€˜ah emphasizes the protection of religion, life, intellect, lineage, and property as the fundamental aims of Islamic law, the juridical-normative approach views law as a set of standards that must be followed to ensure certainty and order. The findings indicate that both approaches complement each other in achieving justice, benefit, and legal certainty. Modern dynamicsâ€”such as digitalization, blockchain technology, personal data protection, and legal institutional reformâ€”require more contextual and adaptive interpretation. Integrating the values of maqÄá¹£id into positive law is considered capable of enhancing the legal systemâ€™s responsiveness to social developments and societal demands. This study concludes that strengthening maqÄá¹£id al-sharÄ«â€˜ah within regulations and judicial practices is a strategic step toward building a legal system that is humanistic, transformative, and oriented toward public welfare.